Evaluation of Pancreatic Fibrosis With Acoustic Radiation Force Impulse Imaging and Automated Quantification of Pancreatic Tissue Components. Issue 10 (November 2018) - Fujita, Yusuke; Kitago, Minoru; Abe, Tokiya; Itano, Osamu; Shinoda, Masahiro; Abe, Yuta; Yagi, Hiroshi; Hibi, Taizo; Ishii, Masatsugu; Nakano, Yutaka; Okuma, Kiyoshi; Hashimoto, Masahiro; et al.
Abstract : Objectives: The aim of this study was to determine whether computer-assisted digital analysis and acoustic radiation force impulse (ARFI) imaging were useful for assessing pancreatic fibrosis, and if ARFI imaging predicted postoperative pancreatic fistula (POPF). Methods: Seventy-eight patients scheduled to undergo pancreatic resection were enrolled. Shear wave velocity (SWV) at the pancreatic neck was measured preoperatively using ARFI imaging. Pancreatic tissue components on a whole slide image were quantified using an automatic image processing software. The relationship between SWV, fibrotic tissue content, and POPF incidence and clinical severity was analyzed. Results: The median collagen fiber, fatty tissue, and acinar cell contents were 11.6%, 8.5%, and 61.3%, respectively. Unlike fatty tissue, collagen fiber content and acinar cells were correlated with SWV ( ρ = 0.440, P < 0.001 and ρ = −0.428, P < 0.001, respectively). Although collagen fiber content and SWV were associated with the overall incidence of POPF ( P = 0.004 and 0.001, respectively), collagen fiber content and SWV had no statistical correlation with clinically relevant POPF ( P = 0.268 and 0.052, respectively). Conclusions: We objectively quantified the pancreatic tissue components using an automatic image processing software. Shear wave velocity was significantly related to collagen fiber content and suggests that ARFI imaging can be useful for evaluating pancreatic fibrosis. Abstract : Supplemental digital content is available in the text.